Study on the socio-economic condition and productive performances of backyard chicken in some selected areas of Pabna district - Sumy, MC; Khokon, MSI; Islam, MM; Talukder, S (Journal of the Bangladesh Agricultural University, 2010)
The study was carried out to investigate backyard chicken production systems in three areas (Bera, Santhia and Sujanagar Thana) of Pabna district. A total of 150 households were selected, from three thana, each having 5 villages and 10 households per village. Stratified random sampling technique was followed to collect data. The hatchability rate was 89, 88.5 and 85 percent in Sujanagar, Santhia and Bera, respectively. The percentage of egg production was 68% in Sujanagar, 72% in Santhia and 75% in Bera Thana. The differences in hatchability and egg production between the three areas were significant. Family wise and per bird total income was Tk. 2124.00 and Tk. 223.95, respectively which is higher than the net cost of Tk. 1324.23 and Tk. 138.70, respectively. The BCR (Benefit Cost Ratio) in family wise and per bird wise was 1.60 and 1.61 respectively. It indicates that if backyard chicken rearers invest Tk.1.0 then they can earn Tk.1.60. So, family wise profit was Tk. 0.60 & per bird basis was Tk. 0.61. The results indicate that backyard chicken rearing is profitable for the farmers in those areas. Vaccinations and balanced diets have a decisive effect on chicken rearing, providing quality products for human consumption and reducing nutritional deficiencies and poverty of the country. Keywords: Backyard chicken; Egg production; Hatchability; Benefit cost ratio DOI: 10.3329/jbau.v8i1.6397 J. Bangladesh Agril. Univ. 8(1): 45-50, 2010